Будова і властивості стекол системи Hg–As–S - Олексеюк, И. Д.; Olekseyuk, I. D.; Парасюк, О. В.; Parasyuk, O. V.; Пискач, Л. В.; Piskach, L. V.; Горгут, Г. П.; Gorgut, G. P.; Климук, Т. Л.; Klymuk, Т. L. (Волинський національний університет ім. Лесі Українки, 2010)
Шляхом накладання проекції поверхні ліквідуса системи Hg–As–S на область склоутворення в ній, вияв- лено вплив послідовності формування структурних одиниць на властивості та будову стекол. The influence of the order of the formation of the structural units on the properties and the structure of the glasses of the Hg–As–S system was determined by overlaying the liquidus surface projection of the system onto its glass-formation region.
Structure and Properties of the Glasses in the Hg–As–S System.
Keywords: область стеклообразования; glass-formation region; проекция поверхности ликвидуса; liquidus surface projection; свойства и строение стекол; properties and structure of the glasses